Overall adjustment acupuncture improves osteoporosis and exerts an endocrine-modulating effect in ovariectomized rats - Li, Xiang; Wu, Kenan; Dong, Qinzuo; Chen, Hongxi; Li, Chunyan; Ren, Zeqin; Liu, Fan; Yue, Xianwu; Xia, Chunlin; Wang, Yuanfeng; Luo, Yingjing; Li, Li; et al. (Frontiers in Endocrinology, 2022)
Background Acupuncture is a widely practiced, convenient, and safe treatment modality within complementary and integrative medicine. Increasing studies have revealed the efficacy of acupuncture for the treatment of osteoporosis in both human and non-human subjects. The aim of the present study was to assess the improvement of osteoporosis after overall adjustment acupuncture (OA) as well as its endocrine-modulating effect in an ovariectomized rat model. Methods In total, 32 female Sprague–Dawley (SD) rats were randomly divided into the sham, model, ovariectomy+estrogen (OVX+E), and OVX+OA (OVX+A) groups with eight rats in each group. The postmenopausal osteoporosis (PMOP) rat model was induced by bilateral ovariectomy. At 12 weeks after surgery, rats in the OVX+E group received estradiol (0.2 mg/kg/i.g./qod) for 12 weeks, and rats in the OVX+A group were treated with acupuncture at Zusanli (ST36), Shenshu (BL23), and Dazhu (BL11) points (qod) for 12 weeks. At the end of the treatment, all rats were sacrificed, and the body weight, uterus index, bone mineral density (BMD), bone mineral content (BMC), bone trabeculae structural parameters, femoral biomechanical properties, femoral histomorphology, and several hormone levels were examined. Results In OVX rats, OA abrogated the body weight gain and improved osteoporosis in terms of BMD, BMC, bone trabeculae structural parameters, bone strength, and bone tissue histomorphology. Moreover, OA modulated the serum levels of estradiol, corticotropin releasing hormone (CRH), adrenocorticotropic hormone (ACTH), and corticosterone (CORT). Conclusions OA improves osteoporosis and exerts an endocrine-modulating effect in ovariectomized rats.